Absence of miRNA-146a Differentially Alters Microglia Function and Proteome - Martin, Nellie A.; Hyrlov, Kirsten H.; Elkjaer, Maria L.; Thygesen, Eva K.; Wlodarczyk, Agnieszka; Elbaek, Kirstine J.; Aboo, Christopher; Okarmus, Justyna; Benedikz, Eirikur; Reynolds, Richard; Hegedus, Zoltan; Stensballe, Allan; et al. (Frontiers in Immunology, 2020)
Background: MiR-146a is an important regulator of innate inflammatory responses and is also implicated in cell death and survival. Methods: By sorting CNS resident cells, microglia were the main cellular source of miR-146a. Therefore, we investigated microglia function and phenotype in miR-146a knock-out (KO) mice, analyzed the proteome of KO and wild-type (WT) microglia by LC-MS/MS, and examined miR-146a expression in different brain lesions of patients with multiple sclerosis (MS). Results: When stimulated with LPS or myelin in vitro, microglia from KO mice expressed higher levels of IL-1β, TNF, IL-6, IL-10, CCL3, and CCL2 compared to WT. Stimulation increased migration and phagocytosis of WT but not KO microglia. CD11c+ microglia were induced by cuprizone (CPZ) in the WT mice but less in the KO. The proteome of ex vivo microglia was not different in miR-146a KO compared to WT mice, but CPZ treatment induced differential and reduced protein responses in the KO: GOT1, COX5b, CRYL1 and cystatin-C were specifically changed in KO microglia. We explored discriminative features of microglia proteomes: sparse Partial Least Squares-Discriminant Analysis showed the best discrimination when control and CPZ-treated conditions were compared. Cluster of ten proteins separated WT and miR-146a KO microglia after CPZ: among them were sensomes allowing to perceive the environment, Atp1a3 that belongs to the signature of CD11c+ microglia, and proteins related to inflammatory responses (S100A9, Ppm1g). Finally, we examined the expression of miR-146a and its validated target genes in different brain lesions of MS patients. MiR-146 was upregulated in all lesion types, and the highest expression was in active lesions. Nineteen of 88 validated target genes were significantly changed in active lesions, while none were changed in NAWM. Conclusion: Our data indicated that microglia is the major source of miR-146a in the CNS. The absence of miR-146a differentially affected microglia function and proteome, and miR-146a may play an important role in gene regulation of active MS lesions.